ANALISIS KELAYAKAN USAHATANI PADI SAWAH DI KECAMATAN UMALULU KABUPATEN SUMBA TIMUR - Noverdisa Putra Adelvos; Elsa Christin Saragih (Fakultas Pertanian, Universitas Janabadra, 2024)
This research aims to analyze the amount of income and feasibility of lowland rice farming. The research was conducted in Umalulu District, East Sumba Regency, from January 2024 to March 2024. The number of samples in this study was 92 farmers, and the sampling technique was carried out using the Proportional Sampling method (balanced sample). To find out the amount of farmers' income, an analysis of business income is carried out, and to find out the level of feasibility of farming, an R/C Ratio analysis is carried out. The results of the income analysis explain that the average income of lowland rice farming in Umalulu District during one planting season is 33,837,268/ha. The results of the feasibility analysis for lowland rice farming in Umalulu District are 7.36, which means that for every IDR 1 spent, farmers will receive a revenue of IDR 7. This value is greater than 1, so that lowland rice farming in Umalulu District is declared feasible.